A Hermeneutical-Theological Analysis of the Nephilim in Genesis 6:4: A Pentecostal Systematic Theology Approach - Rachmat Tony SinjoBantaeng; Candra Gunawan Marisi (DIEGESIS: Jurnal Teologi Kharismatika, 2026)
The Nephilim have long been a controversial topic in biblical theology and can give rise to conflict due to differing interpretations across various denominations, which in turn can weaken the unity of the body of Christ. One interpretation holds that the Nephilim were giants resulting from relations between human and spiritual beings, while another view argues that the Nephilim were simply large humans with no connection to spiritual entities. The question is whether Pentecostal believers, as part of the body of Christ, can respond more wisely to the existing differences in interpretation and discover alternative interpretations by using qualitative research methods, literature review, and exposition of biblical texts through a hermeneutical-theological study with a Pentecostal systematic approach? This study is limited to understand the Nephilim according to what is written in the canonical Indonesian Bible (Terjemahan Baru by Lembaga Alkitab Indonesia TB-LAI), without relying on conclusions drawn from apocryphal writings. The urgency of this research lies in its effort to offer a Pentecostal systematic approach to Nephilim theology, highlighting the root cause of humanity’s fall as rebellion against God and the restoration of the church through the work of the Holy Spirit, who guides and leads the new men to live as sons of God. The results of this study demonstrate that the Bible, under the guidance of the Holy Spirit, is capable of providing answers to the theology of the Nephilim and adequately explaining the identity of the sons of God in a way that supports the growth of Pentecostal believers’ faith in the dynamics of the modern era. Abstrak Nevilim telah lama menjadi topik yang kontroversial dalam teologi biblika dan dapat menimbulkan pertentangan karena perbedaan penafsiran dari berbagai denominasi, yang ujungnya dapat melemahkan persatuan kesatuan tubuh Kristus. Ada penafsiran mengatakan Nevilim adalah makhluk raksasa dikarenakan hubungan antara anak-anak manusia dengan makhluk roh, dan ada juga penafsiran bahwa Nevilim hanyalah anak-anak manusia berbadan raksasa yang tidak ada hubungannya dengan makhluk roh. Pertanyaannya apakah insan Pentakosta yang adalah bagian dari tubuh Kristus dapat menyikapi perbedaan penafsiran yang ada dengan lebih bijak dan menemukan penafsiran alternatif dengan menggunakan metode penelitian kualitatif tinjauan pustaka dan eksposisi teks-teks Alkitab melalui kajian hermeneutis-teologis dengan pendekatan sistematika Pentakosta? Penelitian ini dibatasi pada pemahaman Nevilim menurut Alkitab kanon standar Terjemahan Baru yang diterbitkan Lembaga Alkitab Indonesia (TB-LAI), tanpa perlu bergantung pada hasil akhir dari tulisan-tulisan apokrifa. Urgensi penelitian ini terletak pada upaya menawarkan respons pendekatan Sistematika Pentakosta terhadap teologi Nevilim yang menyoroti akar penyebab kejatuhan manusia sebagai pemberontakan manusia terhadap Allah dan pemulihan gereja melalui karya Roh Kudus yang membimbing, memimpin manusia baru untuk hidup sebagai anak-anak Allah. Hasil dari penelitian ini membuktikan bahwa Alkitab dengan tuntunan Roh Kudus mampu memberikan jawaban akan teologi Nevilim dan menjelaskan predikat anak-anak Allah secara memadai untuk mendukung pertumbuhan iman umat Pentakosta dalam dinamika zaman modern ini.